Effect of nanoclay on the mechanical properties of kenaf fibre reinforced polylactic acid hybrid biocomposite - Anuar, Hazleen (s.n, 2012)
In this research work, PLA-kenaf-nanoclay hybrid composite had been developed through extrusion process. This extrusion process took place in a twin screw extruder machine and the processing parameters involved were classified as processing temperature and processing speed. The temperature was set between 180 to 190 ºC and the screw speed was 100 rpm. PLA, kenaf and organo montmorillonite (OMMT) clay were the main materials involved in developing hybrid composite. For this reason, three different processes were developed which are identified as PLA-kenaf-OMMT single extrusion, PLA-kenaf-OMMT double extrusion (PLA and kenaf extruded first then OMMT was added) and PLA-OMMT-kenaf double extrusion (PLA and OMMT extruded first then kenaf was added). Kenaf fiber and nanoclay enhanced the mechanical properties of PLA biocomposite in double extrusion process.